2020
DOI: 10.18280/ts.370505
|View full text |Cite
|
Sign up to set email alerts
|

Retinex-Based Multiphase Algorithm for Low-Light Image Enhancement

Abstract: These days, digital images are one of the most profound methods used to represent information. Still, various images are obtained with a low-light effect due to numerous unavoidable reasons. It may be problematic for humans and computer-related applications to perceive and extract valuable information from such images properly. Hence, the observed quality of low-light images should be ameliorated for improved analysis, understanding, and interpretation. Currently, the enhancement of low-light images is a chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…To evaluate the effectiveness of the proposed enhancement algorithm, we compare the proposed method with conventional image enhancement algorithms and state-of-the-art technologies, i.e., multi-scale retinex (MSR) [ 7 ], multi-scale retinex with color restoration (MSRCR) [ 8 ], retinex-based Multiphase algorithm (RBMP) [ 23 ], and adaptive image enhancement method (AIEM) [ 22 ]. Six representative images with uneven illumination (image #1–6) are selected from the MEF [ 24 ] and NPE [ 18 ] image sets and combined with four nighttime images actually taken as the experimental test images (image #7–10).…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…To evaluate the effectiveness of the proposed enhancement algorithm, we compare the proposed method with conventional image enhancement algorithms and state-of-the-art technologies, i.e., multi-scale retinex (MSR) [ 7 ], multi-scale retinex with color restoration (MSRCR) [ 8 ], retinex-based Multiphase algorithm (RBMP) [ 23 ], and adaptive image enhancement method (AIEM) [ 22 ]. Six representative images with uneven illumination (image #1–6) are selected from the MEF [ 24 ] and NPE [ 18 ] image sets and combined with four nighttime images actually taken as the experimental test images (image #7–10).…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Additionally, the figure depicts respective image histograms for each method. Different algorithms are the low-light image enhancement (LIME) algorithm [42], the Retinex based multiphase (RBM) algorithm [43], the bio-inspired multi-exposure fusion (BIMEF) algorithm [44], and the Zohair algorithm [45]. Upon applying various enhancement methods, it is observed that the peaks of histogram shift to the right, indicating an improvement in image brightness.…”
Section: The Evaluation Of Image Enhancement Methodsmentioning
confidence: 99%
“…In order to verify the superiority of the proposed algorithm in processing nighttime images, Ammen [ 27 ], Dong [ 28 ], SRIE [ 29 ], NPE [ 22 ], MF [ 15 ], Jiep [ 30 ], Ying [ 31 ], LIME [ 32 ], AIEM [ 7 ], and RBMP [ 33 ] have been chosen as the comparison algorithms. Nighttime images in the dataset of literature [ 34 ], which have a lot of dark light regions and contain artificial light sources, are selected to evaluate the proposed algorithm.…”
Section: Methodsmentioning
confidence: 99%